Fiscal Consolidation and its Cross-Country Effects - Apostolis Philippopoulos; Petros Varthalitis; Vanghelis Vassilatos (Center for Economic Studies and ifo Institute (CESifo), 2016)
We build a new Keynesian DSGE model consisting of two heterogeneous countries participating in a monetary union. We study how public debt consolidation in a country with high debt (like Italy) affects welfare in a country with solid public finances (like Germany). Our results show that debt consolidation in the high-debt country benefits the country with solid public finances over all time horizons. By constrast, in Italy, namely the country that takes the consolidation measures, such a policy is productive only in the medium and long term. Thus, although there is a conflict of national interests in shorter horizons, there is a common interest in the medium and long term. All this is with optimized feedback policy rules. By contrast, debt consolidation is welfare inferior to non-consolidation for both countries and all the time, if it is implemented in an ad hoc way, like an increase in income taxes. Therefore, the policy mix is important.
Keywords: E60; F30; H60; 330; debt consolidation; Country spillovers; feedback policy rules; new Keynesian